2006
DOI: 10.1099/vir.0.81614-0
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic analysis of the precore/core gene of hepatitis B virus genotypes E and A in West Africa: new subtypes, mixed infections and recombinations

Abstract: One hundred and twenty-two new hepatitis B virus (HBV) preC/C sequences and three complete genomes from three major countries in West Africa were analysed. The majority of sequences were of genotype E and the only other genotype found was genotype A. Although for genotype E sequences, the genetic diversity of the preC/C gene was about two to three times higher than that of the preS/S gene, it was still considerably lower than that for genotype A sequences. The HBV/E preC/C gene was related most closely to subg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

21
171
3

Year Published

2007
2007
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 134 publications
(195 citation statements)
references
References 39 publications
21
171
3
Order By: Relevance
“…Elsewhere in Africa, several hybrid strains have been described as involving HBV/E and genotypes A, D and G (Bekondi et al, 2007;Garmiri et al, 2009;Kurbanov et al, 2005;Laoi & Crowley, 2008;Meldal et al, 2009;Mulders et al, 2004;Olinger et al, 2006). Molecular analyses often found these same recombinant sites.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Elsewhere in Africa, several hybrid strains have been described as involving HBV/E and genotypes A, D and G (Bekondi et al, 2007;Garmiri et al, 2009;Kurbanov et al, 2005;Laoi & Crowley, 2008;Meldal et al, 2009;Mulders et al, 2004;Olinger et al, 2006). Molecular analyses often found these same recombinant sites.…”
Section: Discussionmentioning
confidence: 96%
“…For example, a recombinant between HBV/C and HBV/D is the dominant subgenotype circulating in Tibet (Cui et al, 2002). In Africa, such recombination events have also been described, including recombinants A-D (Owiredu et al, 2001), A-E (Garmiri et al, 2009;Kurbanov et al, 2005), D-E-A and the G insertion (Olinger et al, 2006). Very recently, new HBV/ D-E recombinants were identified in the Central African Republic, Ireland (in a west African patient), Tunisia and Guinea, with all of them sharing the same recombination profile (Bekondi et al, 2007;Garmiri et al, 2009;Laoi & Crowley, 2008;Meldal et al, 2009).…”
Section: Introductionmentioning
confidence: 98%
“…Genotypes/subgenotypes have distinct geographical distributions: HBV/A and HBV/D are found worldwide, HBV/B and HBV/C are found in east/south-east Asia, HBV/E in west/central Africa, and HBV/F and HBV/H in native populations of the Americas (Araujo et al, 2011; Kramvis et al, 2005). HBV/G was described by Stuyver et al (2000) and, despite low prevalence, seems ubiquitous, as it has been reported in Europe (Lacombe et al, 2006;Vieth et al, 2002), the Americas (Alvarado-Esquivel et al, 2006;Alvarado Mora et al, 2011;Bottecchia et al, 2008;Chu et al, 2003;Osiowy et al, 2008), Asia (Shibayama et al, 2005;Toan et al, 2006) and Africa (Olinger et al, 2006;Toan et al, 2006). HBV/G is frequently reported in patients infected with human immunodeficiency virus (HIV) (Dao et al, 2011;Zehender et al, 2003), particularly in men who have sex with men (MSM) (Bottecchia et al, 2008;Osiowy et al, 2008).…”
mentioning
confidence: 95%
“…Using different methods for genotyping, several reports described high rates of double infection with two different HBV genotypes in all parts of the world. Using these methods double infections have been found in 4.4% [56] , 10.9% [57] , 12.5% [58] , 14.1% (Kirschberg et al, unpublished results), 17.3% [59] and 17.5% [60] of HBV infected patients. Even triple infections with HBV of genotype A, B and C have been described in 0.9% of HBV infected intravenous drug users [60] .…”
Section: Double Infections and Recombi-nantsmentioning
confidence: 99%